Magnetohydrodynamic Calculation for Electromagnetic Stirring Coupling Fluid Flow and Solidification in Continuously Cast Billets. Issue 11 (14th June 2017) - Dong, Qipeng; Zhang, Jiongming; Liu, Qiang; Yin, Yanbin
Abstract : A new magnetohydrodynamic (MHD) model considering flow field and solidification is developed to simulate electromagnetic stirring (EMS) during billet continuous casting. Based on the model, the influence of fluid flow on the calculation of magnetic field, induced current, and electromagnetic force is investigated in comparison to the traditional calculation model. Furthermore, the characteristics of fluid flow affected by electromagnetic stirring, including three‐dimensional streamlines, tangential velocity, and meniscus fluctuation, are studied to evaluate the new MHD model. The MHD calculation reveals that the flow field in mold has a certain influence on the magnetic field, while the effect resulting from the interaction between flow field and magnetic field on the electromagnetic force is significant. As a consequence, increased velocity at the meniscus has been obtained compared to the traditional calculation, indicating a more intense meniscus fluctuation. Abstract : A new MHD model considering the interaction between fluid flow and magnetic field was developed, and the distinction in the predicted results of electromagnetic field and electromagnetically driven flow in comparison with the traditional calculation was further investigated. Results of the new model show a significant distinction in the characteristics of electromagnetic force, and the relatively slight effect on the flow field.